Implementing Partial Tax Harmonization in an Asymmetric Tax Competition Game with Repeated Interaction - Jun-ichi Itaya; Makoto Okamura; Chikara Yamaguchi (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper investigates the conditions under which partial harmonization for capital taxation is sustained in a repeated interactions model of tax competition when there are three countries with heterogenous capital endowments. We show that regardless of the structure of the coalition (i.e. full or partial tax coordination), whether partial tax harmonization is sustainable or not crucially depends on the extent to which the capital endowment of the medium-sized country is similar to that of the large or small country. The most noteworthy finding is that the closer the capital endowment of the median country is to the average one, the less likely the tax harmonization including the median country is to prevail and the more likely the partial tax harmonization excluding the median country is to prevail. We also show that partial tax harmonization makes the member countries of the tax union better off and non-member countries worse off, which stands in shape contrast with previous studies such as Konrad and Schjelderup (1999) and Bucovetsky (2009).
Keywords: H73; F59; F21; 330; tax coordination; asymmetric countries; repeated game; tax competition